2021
DOI: 10.1103/physrevfluids.6.113902
|View full text |Cite
|
Sign up to set email alerts
|

Effects of parietal suction and injection on the stability of the Blasius boundary-layer flow over a permeable, heated plate

Abstract: The main concern of this paper is to investigate the effects on the stability behavior of wall suction or injection for external boundary-layer flow over a heated, porous plate for a fluid with temperature-dependent viscosity. The wall suction or injection are applied to the flow by a simple modification for the no-penetration condition and the current boundary conditions on the flat plate. Liquid-type viscosities are found to entrain both the velocity and temperature profiles closer to the plate with increasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…We also observed that shifting from injection to suction stabilized the flow. However, our results are consistent with Al-Malki 41 for Blasius flow, in that suction causes a stabilisation of the type II cross-flow instability mode. When we compared the asymptotic results of types I with II modes, we concluded that increasing T s to a positive value destabilizes the type I modes and stabilizes the type II modes for a flow over a rotating disk and vice versa.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…We also observed that shifting from injection to suction stabilized the flow. However, our results are consistent with Al-Malki 41 for Blasius flow, in that suction causes a stabilisation of the type II cross-flow instability mode. When we compared the asymptotic results of types I with II modes, we concluded that increasing T s to a positive value destabilizes the type I modes and stabilizes the type II modes for a flow over a rotating disk and vice versa.…”
Section: Discussionsupporting
confidence: 90%
“…Collectively, increasing W * from negative to positive shifted the curves at type I and II upwards (figure ( 14)). Our data are consistent with Al-Malki 41 for Blasius flow, where suction stabilized the type I cross flow instability mode. Importantly, expanding the inviscid type I and viscous type II modes provided the capacity to consider non-parallel effects.…”
Section: Please Cite This Article Assupporting
confidence: 89%
“…However, in the compressible scheme, the physics of the fluid largely stayed in the ideal gas regime due to the erstwhile aerodynamic demand. On the other hand, the O–S framework has been extended to account for temperature-dependent viscosity 17 , 18 , coupling with various controlling methods 19 . In line with the emphasis on viscosity, viscosity-stratified flows amount to a particular type that attracted significant attention 20 .…”
Section: Resultsmentioning
confidence: 99%
“…An exponential map of the Gauss-Lobatto grid points is adopted for the Chebyshev polynomials at a number of points into the physical domain: 100 points are sufficient to achieve accurate results such as results of previous studies, which are validated by confirming 100 points distributed between the geometry surface z = 0 and the top of the domain η max = 20 using the spectral method based on Chebyshev polynomials such as. 5,[30][31][32] Our simulations were run with a variable number of collocation points e.g. 110 or 120 and also η max was varied e.g.…”
Section: A Formulationmentioning
confidence: 99%
“…The delay of transition has a particular interest to stabilise laminar flows, where this idea has been investigated extensively. There is a number of interesting examples that include: suction, mean flow distortion, surface roughness and wave cancellation by superposition (see [2][3][4][5] ). These investigations could be intelligent strategies in most technological applications to delay the laminar-turbulent transition process in mechanism of fluid flow.…”
Section: Introductionmentioning
confidence: 99%